An Investigation on the Prevalence of Maintenance Workers Practicing or Applying Lockout Tagout During Maintenance Process - Omar, Arisha; Yap Soon Ping,; Sahak, Nurrul Hafeezah (Progress in Engineering Application and Technology, 2024)
Manufacturing industry has many machines and equipment that require frequent maintenance, repair, and service. The presence of dangerous sources of energy such as electricity, mechanical, hydraulic, pneumatic, chemical, thermal or other in machines and equipment can be dangerous for workers. National standards in numerous countries emphasize the necessity of managing hazardous energy associated with machinery to prevent unforeseen events triggered by the sudden release of energy. This study aimed to determine the prevalence of maintenance workers practicing or applying lockout tagout during maintenance process. The quantitative data gathered through the questionnaires were analysed using the Statistical Package for Social Sciences (SPSS) software, employing descriptive analysis. The qualitative interviews were utilized to enrich the research findings and provide supporting information for the proposed LOTO procedure for this manufacturing industry. The results indicated that maintenance workers have a high (93.3%) level of practicing and applying LOTO during machine maintenanc process. This research offers a valuable contribution in determine the percentage of the maintenance worker practices on LOTO due to prevent incidents and risks occur towards workers, property, and the environment.